Evaluation of Water Storage Change of Inland Cryosphere in Northwestern China - Min Xu; Shichang Kang; Jiazhen Li (Advances in Meteorology)
The Gravity Recovery and Climate Experiment (GRACE) satellite mission provides measurements of Earth’s static and time-variable gravity fields with monthly resolution. In this study, changes of water storage in northwestern China were determined by GRACE monthly gravity field data obtained from 2003 to 2010. Comparisons of water storage change (WSC) simulated by a four-dimensional assimilation model (Noah) and observed by GRACE revealed similar patterns of change and a correlation coefficient of 0.71 (P<0.05). Trend analysis indicated significant changes in the spatiotemporal variation of WSC in northwestern China during the 8-year study period, which were stronger in the east than in the west and more pronounced in the south than in the north. The most pronounced increase in water storage occurred in Gansu and Qinghai provinces, but, overall, water storage increased by 0.61 mm/a over northwestern China during the study period. Clear seasonal variations of WSC and precipitation were found, because glacial meltwater and precipitation are the main sources of water in the hydrosphere; meanwhile, the distributions of glaciers and permafrost also affect the spatial distribution of WSC.